Development of ultra-short PCR assay to reveal BRAF V600 mutation status in Thai colorectal cancer tissues. - Nunthawut Chat-Uthai; Pichpisith Vejvisithsakul; Sutthirat Udommethaporn; Puttarakun Meesiri; Chetiya Danthanawanit; Yannawan Wongchai; Chinachote Teerapakpinyo; Shanop Shuangshoti; Naravat Poungvarin (PLoS ONE)
The protein kinase BRAF is one of the key players in regulating cellular responses to extracellular signals. Somatic mutations of the BRAF gene, causing constitutive activation of BRAF, have been found in various types of human cancers such as malignant melanoma, and colorectal cancer. BRAF V600E and V600K, most commonly observed mutations in these cancers, may predict response to targeted therapies. Many techniques suffer from a lack of diagnostic sensitivity in mutation analysis in clinical samples with a low cancer cell percentage or poor-quality fragmented DNA. Here we present allele-specific real-time PCR assay for amplifying 35- to 45-base target sequences in BRAF gene. Forward primer designed for BRAF V600E detection is capable of recognizing both types of BRAF V600E mutation, i.e. V600E1 (c.1799T>A) and V600E2 (c.1799_1800delTGinsAA), as well as complex tandem mutation caused by nucleotide changes in codons 600 and 601. We utilized this assay to analyze Thai formalin-fixed paraffin-embedded tissues. Forty-eight percent of 178 Thai colorectal cancer tissues has KRAS mutation detected by highly sensitive commercial assays. Although these DNA samples contain low overall yield of amplifiable DNA, our newly-developed assay successfully revealed BRAF V600 mutations in 6 of 93 formalin-fixed paraffin-embedded colorectal cancer tissues which KRAS mutation was not detected. Ultra-short PCR assay with forward mutation-specific primers is potentially useful to detect BRAF V600 mutations in highly fragmented DNA specimens from cancer patients.